2022
DOI: 10.3389/fpsyt.2022.879491
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Effects of Different Types of Probiotics in Animal Alzheimer's Disease Studies

Abstract: Alzheimer's disease (AD) is a global public health priority as with aging populations, its prevalence is expected to rise even further in the future. The brain and gut are in close communication through immunological, nervous and hormonal routes, and therefore, probiotics are examined as an option to influence AD hallmarks, such as plaques, tangles, and low grade inflammation. This study aimed to provide an overview of the available animal evidence on the effect of different probiotics on gut microbiota compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 101 publications
(253 reference statements)
0
14
0
1
Order By: Relevance
“…Intestinal microbiota imbalance is common in AD patients ( van Olst et al, 2021 ) and has been reported in APP/PS1 transgenic mice and 5✕FAD transgenic mice ( Zhang et al, 2017 ; Liu et al, 2021 ). Studies have shown that restoring the intestinal microbiota is effective in improving AD ( de Rijke et al, 2022 ; Snigdha et al, 2022 ). Therefore, the mechanism of improving AD by modulating insulin signaling in the brain may be related to restoring the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbiota imbalance is common in AD patients ( van Olst et al, 2021 ) and has been reported in APP/PS1 transgenic mice and 5✕FAD transgenic mice ( Zhang et al, 2017 ; Liu et al, 2021 ). Studies have shown that restoring the intestinal microbiota is effective in improving AD ( de Rijke et al, 2022 ; Snigdha et al, 2022 ). Therefore, the mechanism of improving AD by modulating insulin signaling in the brain may be related to restoring the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Given that AD pathology and neuropsychiatric disorders are associated with dysbiosis in gut microbiota, treatments with different compositions of probiotics have been explored in therapeutic trials. There are several systematic reviews of these interventions in human patients [49,50] as well as in experiments with AD mice [51]. Briefly, it has been commonly observed that probiotic treatments are able to improve cognitive functions in both MCI and AD patients.…”
Section: Microbiota Gut-brain Axis In Ad Pathogenesismentioning
confidence: 99%
“…A study summarized the evidence of the relationship between the intestinal microflora, cognitive function, and dementia pathology in the elderly, and its conclusion supported the impact of intestinal microorganisms on cognitive function. In animal studies, prebiotics and probiotics had a positive effect on cognitive function ( Neta et al., 2022 ; de Rijke et al., 2022 ), but the existing evidence is insufficient to support a clinical application ( Ticinesi et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%